The Berlin-Brandenburg Air Study—A Methodological Study Paper of a Natural Experiment Investigating Health Effects Related to Changes in Airport-Related Exposures - Vanessa Soppa; Sarah Lucht; Sarah Lucht; Katherine Ogurtsova; Anna Buschka; Mónica López-Vicente; Mónica López-Vicente; Mónica López-Vicente; Mónica López-Vicente; Mònica Guxens; Mònica Guxens; Mònica Guxens; et al. (International Journal of Public Health, 2023)
Objectives: This paper presents the study design of the Berlin-Brandenburg Air study (BEAR-study). We measure air quality in Berlin and Brandenburg before and after the relocation of aircraft (AC) traffic from Tegel (TXL) airport to the new Berlin-Brandenburg airport (BER) and investigate the association of AC-related ultrafine particles (UFP) with health outcomes in schoolchildren.Methods: The BEAR-study is a natural experiment examining schoolchildren attending schools near TXL and BER airports, and in control areas (CA) away from both airports and associated air corridors. Each child undergoes repeated school-based health-examinations. Total particle number concentration (PNC) and meteorological parameters are continuously monitored. Submicrometer particle number size distribution, equivalent black carbon, and gas-phase pollutants are collected from long-term air quality monitoring stations. Daily source-specific UFP concentrations are modeled. We will analyze short-term effects of UFP on respiratory, cardiovascular, and neurocognitive outcomes, as well as medium and long-term effects on lung growth and cognitive development.Results: We examined 1,070 children (as of 30 November 2022) from 16 schools in Berlin and Brandenburg.Conclusion: The BEAR study increases the understanding of how AC-related UFP affect children’s health.